Omnichannel Strategy and Customer Experience on Purchase Decisions: Trust as Mediating Variable - Selmi Dedi; Yulius Heri Saptomo; Dirarini Sudarwari (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Digital transformation has reshaped consumer behavior, encouraging cosmetics retailers to adopt omnichannel strategies and enhance customer experience. However, limited research has examined the mediating role of trust in the relationship between omnichannel strategy, customer experience, and purchase decisions within local cosmetics retail contexts. Objective: This study examines the effects of omnichannel strategy and customer experience on purchase decisions at Rain Cosmetic Stores, with trust as a mediating variable. Methods: A quantitative explanatory research design was employed. Data were collected from 100 Rain Cosmetic consumers using purposive sampling and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0 to evaluate direct and indirect relationships among variables. Results: Omnichannel strategy significantly influences trust (β = 0.354, p = 0.004) but does not significantly affect purchase decisions (β = 0.133, p = 0.340). Customer experience significantly affects trust (β = 0.518, p < 0.001) and purchase decisions (β = 0.559, p < 0.001). Trust does not have a significant effect on purchase decisions (β = 0.231, p = 0.059) and does not mediate the relationship between omnichannel strategy or customer experience and purchase decisions (p > 0.05). These findings indicate that customer experience is the primary driver of purchase decisions, whereas trust plays a limited mediating role. Conclusion: Customer experience is the strongest determinant of purchase decisions, while omnichannel strategy primarily contributes to trust development rather than directly influencing purchasing behavior. Trust does not significantly translate into purchase decisions, suggesting that experiential factors have a greater influence than perceived credibility in shaping consumer decisions within this context.